A tutela jurídica do consumidor superendividado à luz do princípio da dignidade da pessoa humana - Vieira, Lara Fernandes (2013)
The phenomenon of over-indebtedness of the individual consumer is considered a serious social, economic and legal problem in contemporary capitalist societies. The indebtedness is characterized by the inability of the consumer natural person, in good faith, to pay its overdue and upcoming debts, not including professional debts, tax debts, family support, or debts resulting from a criminal action. The effects of this phenomenon for the consumer are perverse. The consumer’s over-indebtedness affects his/her human dignity, since this situation triggers a social exclusion, not only because of the name on credit protection registration records, but also due to the loss of economic capacity to purchase basic goods and services, the decreased quality of life, the lower self-esteem, and the guilt and shame towards family and friends. For these reasons, the protection of the consumer in a situation of over-indebtedness is absolutely necessary. The goal of this work is to review the problem of over-indebtedness of consumers in Brazil, from the perspective of the principle of human dignity, and the fundamental right to the protection of this principle in view of the urgent need to establish its effective judicial protection, consistent with the National Consumer Relations policy, and the principles of the Code of Consumer Protection. The methodology adopted was exploratory and descriptive, with qualitative approach, based mainly on literature and documents, and applied. To achieve this goal, I first review the phenomenon of indebtedness, including its causes and characteristics, as well as how it affects the lives and the dignity of consumers who find themselves in this situation. Then I address the principle of human dignity, and the fundamental right to the consumer protection conferred by the Constitution of 1988. I will then lay out the evolution of the contract, and the emergence of paradigms from the adoption of the principle of human dignity and its protection by the Constitution. I then analyze domestic and foreign legislation addressing the problem of over-indebtedness. I also propose the adoption of preventive measures for approaching over-indebtedness in Brazil, as well as present experiments conducted in some Brazilian states with this scope, as well as the updated draft of the Code of Consumer Protection. Finally, I argue it is urgent to create the legal protection of over-indebtedness consumers in Brazil, in line with the current constitutional framework, and the values it spouses under the principle of human dignity.